Cumulative biomedical risk and social cognition in the second year of life: prediction and moderation by responsive parenting - Wade, Mark; Madigan, Sheri; Akbari, Emis; Jenkins, Jennifer M. (Frontiers in Psychology, 2015)
At 18 months, children show marked variability in their social-cognitive skill development, and the preponderance of past research has focused on constitutional and contextual factors in explaining this variability. Extending this literature, the current study examined whether cumulative biomedical risk represents another source of variability in social cognition at 18 months. Further, we aimed to determine whether responsive parenting moderated the association between biomedical risk and social cognition. A prospective community birth cohort of 501 families was recruited at the time of the child’s birth. Cumulative biomedical risk was measured as a count of 10 prenatal/birth complications. Families were followed up at 18 months, at which point social-cognitive data was collected on children’s joint attention, empathy, cooperation, and self-recognition using previously-validated tasks. Concurrently, responsive maternal behavior was assessed through observational coding of mother-child interactions. After controlling for covariates (e.g. age, gender, child language, socioeconomic variables), both cumulative biomedical risk and maternal responsivity significantly predicted social cognition at 18 months. Above and beyond these main effects, there was also a significant interaction between biomedical risk and maternal responsivity, such that higher biomedical risk was significantly associated with compromised social cognition at 18 months, but only in children who experienced low levels of responsive parenting. For those receiving comparatively high levels of responsive parenting, there was no apparent effect of biomedical risk on social cognition. This study shows that cumulative biomedical risk may be one source of inter-individual variability in social cognition at 18 months. However, positive postnatal experiences, particularly high levels of responsive parenting, may protect children against the deleterious effects of these risks on social cognition.